2014
DOI: 10.1186/1471-2172-15-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous interleukin-10 alleviates allergic inflammation but inhibits local interleukin-10 expression in a mouse allergic rhinitis model

Abstract: BackgroundInterleukin-10 (IL-10) has an important anti-inflammatory and immunoregulatory function, and its expression is negatively correlated with the development and severity of allergic rhinitis (AR). However, the in vivo effects of exogenous IL-10 on AR have not been studied and the mechanisms underlying the effects of IL-10 have not been fully understood. Here, we investigated the effects of intranasal administration of recombinant mouse (rm) IL-10 on the expression of Th responses and local IL-10 in a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
(51 reference statements)
2
28
0
Order By: Relevance
“…The frequency and total number of CD4 þ T cells expressing IL-4, IL-5, and IL-13 were also significantly increased in the lung and lung-draining mediastinal lymph nodes of Cd4 Cre Il10ra fl/fl mice (Figure 2a-d and Supplementary Figure S1A-D online). Although IL-10 can also regulate both type-1 and type-17 responses following allergen challenge in the airways, 7,20 we found that the frequency of IFNg þ and IL-17A þ T cells in the lung were significantly reduced, with numbers of interferon-g (IFNg)-and IL-17A-producing CD4 þ cells unaffected by the absence of IL-10 signaling in T cells (Figure 2e,f and Supplementary Figure S1C,D). The proportion of Foxp3 þ Treg cells in the local lymph nodes were largely unaffected; however, we did observe an increase in Foxp3 þ Treg cells in the lung of Cd4 Cre Il10ra fl/fl mice (Supplementary Figure S1E,F).…”
Section: Il-10r Signaling In T Cells Regulates Th2 Cell Differentiatimentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and total number of CD4 þ T cells expressing IL-4, IL-5, and IL-13 were also significantly increased in the lung and lung-draining mediastinal lymph nodes of Cd4 Cre Il10ra fl/fl mice (Figure 2a-d and Supplementary Figure S1A-D online). Although IL-10 can also regulate both type-1 and type-17 responses following allergen challenge in the airways, 7,20 we found that the frequency of IFNg þ and IL-17A þ T cells in the lung were significantly reduced, with numbers of interferon-g (IFNg)-and IL-17A-producing CD4 þ cells unaffected by the absence of IL-10 signaling in T cells (Figure 2e,f and Supplementary Figure S1C,D). The proportion of Foxp3 þ Treg cells in the local lymph nodes were largely unaffected; however, we did observe an increase in Foxp3 þ Treg cells in the lung of Cd4 Cre Il10ra fl/fl mice (Supplementary Figure S1E,F).…”
Section: Il-10r Signaling In T Cells Regulates Th2 Cell Differentiatimentioning
confidence: 99%
“…Overall, these data provide new insight into IL-10-mediated regulation of allergic airway inflammation and identify that pathogenic Th2 cells are an important direct target of IL-10. Thus, therapeutic use of IL-10 20,38 to treat airway inflammatory conditions may directly impact antigen-reactive pathogenic T cells, expanding the broad immunosuppressive properties of IL-10.…”
Section: Il-10r Signaling Specifically In Il4 Gfp þ Th2 Cells Regulmentioning
confidence: 99%
“…In recent years, the discovery of Th17 and regulatory T (Treg) cells has added additional layers of complexity to the older Th1/Th2 balance paradigm, and it has expanded our understanding of the pathogenesis of AR [3]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IL-10-deficient mice exhibit reduced numbers of intact mast cells after administration of C48/80, an effect reversed by the administration of recombinant IL-10 ( Bundoc and Keane-Myers, 2007). In addition, administration of recombinant IL-10 in an OVA-induced allergic rhinitis model reduced the influx of eosinophils and mast cells into the nasal mucosa, as well as reducing IL-5 and IL-17 in the nasal lavage fluid (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%